Prognostic significance of serum galectin-3 in predicting cardiovascular outcomes after percutaneous coronary intervention with drug-eluting stents - Choi, Yeon-Jik; Seo, Suk Min (Frontiers in Cardiovascular Medicine, 2025)
BackgroundGalectin-3 is a well-established biomarker on the predictor of cardiovascular events in patients with heart failure. Its pathophysiologic association with inflammation, cell proliferation, and fibrogenesis may implicate serum galectin-3 as a predictor of clinical outcomes in coronary artery disease (CAD) patients undergoing percutaneous coronary intervention (PCI) with drug-eluting stents (DES). The aim of this study was to examine the prognostic value of the galectin-3 level in patients with CAD who underwent PCI with DES.MethodsA total of 939 patients undergoing successful PCI with DES were consecutively enrolled between January 2007 and December 2009. The serum galectin-3 level was measured, classified into two groups according to the median galectin-3 level (9.52 ng/ml, interquartile range 7.31–12.81), and compared with the composite of all-cause mortality, non-fatal myocardial infarction (MI), and stroke.ResultsThe median follow-up duration was 997 days (interquartile range 766–1,264 days). The high galectin-3 group had a significantly higher incidence of all-cause mortality, cardiac mortality, and composite of all-cause mortality, non-fatal MI, and stroke. High galectin-3 was a significant independent predictor of the composite of all-cause mortality, non-fatal MI, and stroke (adjusted hazard ratio 1.670, 95% confidence interval 1.014–2.751, p = 0.044). The addition of the serum galectin-3 level to the conventional clinical risk model improves the model discrimination (C-statistic = 0.694–0.786, p for difference < 0.01), reclassification [continuous net classification improvement (0.297, p < 0.01) and integrated discrimination improvement (0.064, p < 0.01)].ConclusionOur data suggest that serum galectin-3 is an independent predictor of cardiovascular events in patients undergoing PCI with DES.